Peran Kementerian Luar Negeri Republik Indonesia dalam Diplomasi Ekonomi Furnitur: Studi Kasus Jif-Bw di Afrika dan Timur Tengah - Rachel Eunike Lendeng; Triesanto Romulo Simanjuntak; Novriest Umbu Walangara Nau (Institut Nalanda, 2026)
This study aims to explain the role of the Ministry of Foreign Affairs of the Republic of Indonesia in supporting Indonesia’s economic diplomacy through the promotion of the national furniture industry at the Jepara International Furniture Buyer Week (JIF-BW), as an effort to expand export markets to Africa and the Middle East. This research uses a qualitative method with primary data obtained through interviews and secondary data from academic journals, official reports, government documents, and supporting literature. The Indonesian furniture industry is a creative sector with strong potential in international trade due to its product quality, cultural value, and increasing competitiveness. In its development, the Ministry of Foreign Affairs plays a role in economic diplomacy by supporting JIF-BW as a platform for promotion and international networking. This involvement is carried out through coordination with Indonesian Embassies (KBRI), Indonesian Trade Promotion Centers (ITPC), and trade attachés in various countries. The findings show that JIF-BW is not only a promotional event for furniture products but also part of Indonesia’s economic diplomacy strategy to introduce its creative industry to the global market. This activity helps expand international trade networks and enhance the global image of Indonesian furniture, particularly in Africa and the Middle East as key export expansion targets.